Financial Performance Under the Influence of the Coronavirus Disease 2019: Effects of Strategic Flexibility and Environmental Dynamics in Big Data Capability - Chen, Limei; Zhai, Liping; Zhu, Weiwei; Luo, Gongzhi; Zhang, Jing; Zhang, Yaozhen (Frontiers in Psychology, 2021)
This study draws on the dynamic capabilities view and the firm's big data capability (BDC) in the new economic environment. It constructs an adjusted intermediary model to study the mechanism of big data capability, strategic flexibility and environmental dynamic affecting financial performance. We find that strategic flexibility plays an intermediary role in the "Converse-U" relationship between BDC and financial performance. Environmental dynamics adjust the relationship between BDC and financial performance positively and smooth the "Converse-U" relationship. The findings suggest building and managing BDC, combining BDC with the management process, and achieving continuous financial performance improvement in a dynamic environment. The paper also puts forward the nonlinear hypothesis, discusses the "Converse-U" relationship between BDC and enterprise financial performance in the Chinese context of digital economy explosion and growth, and considers the intermediary mechanism of strategic flexibility and the regulatory effect of environmental dynamics.